The Effect of Discipline and Motivation on Employee Performance in SMP Negeri 2 Parigi, Pangandaran District - Suwanto Suwanto (Jurnal Studi Guru dan Pembelajaran, 2020)
This study aims to determine: (1) The effect of work discipline and employee performance at SMP Negeri 2 Parigi Pangandaran Regency, (2) The effect of work motivation and employee performance at SMP Negeri 2 Parigi Pangandaran Regency, (3) The effect of work discipline and work motivation on Employee performance at SMP Negeri 2 Parigi Pangandaran Regency. This research is a survey research with a quantitative approach. This research sample is SMP Negeri 2 Parigi Pangandaran Regency employees, amounting to 70 employees and collecting data using a Likert scale questionnaire. The data analysis technique used is descriptive analysis and inferential analysis, namely: (1) Validity and Reliability Test, (2) Classical Assumption Test, (3) Analysis of the Coefficient of Determination (r²), (4) Correlation Coefficient Analysis, (5) Linear Regression Analysis Simple, (7) Multiple Linear Regression Analysis, (8) Hypothesis Test Analysis with Partial Test (t-test) and Simultaneous Test (f test). Based on this study results, there is a significant influence simultaneously between the variables of work discipline and work motivation on employee performance with an influence of 47.6%.